PENGARUH PENDEKATAN TPACK TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA DI SEKOLAH DASAR - Grignard Hugger Ratuan; Dwi Nurazizah; Rezki Amaliah; Deananda; Nayla Angraeni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of the TPACK (Technological, Pedagogical, and Content Knowledge) approach on student learning outcomes in Mathematics subjects in elementary schools. The method used was a meta-analysis by analyzing 5 relevant national journal articles published between 2020-2024. The data collected included effect size (es) and standard error (se) from each study. Data analysis was performed using JASP software with a random effects model approach (REML, KNAHA adjustment). The meta-analysis results showed a pooled effect size of 1.479 (95% CI: 0.410–2.548; p = 0.018), which is categorized as large and statistically significant. Heterogeneity test results showed I² = 79.41% and Q(4) = 25.46 (p < 0.001), indicating high heterogeneity between studies. The residual funnel plot showed a symmetrical distribution of points, meaning there was no significant publication bias. The 95% prediction interval (PI) ranged from -0.939 to 3.897, which crossed zero, indicating that the effect of TPACK is contextual. In conclusion, the TPACK approach has a significant and positive effect on Mathematics learning outcomes in elementary school students, but its effectiveness highly depends on the implementation context. Further research with a larger number of studies is needed to identify sources of heterogeneity more deeply.